Zumbi assombra quem?, uma rapsódia de allan da rosa, transpondo a barreira da invisibilidade dos corpos pretos - Ribeiro, Olbia Cristina (2023)
In this master's thesis, we analyze the work Zumbi assombra quem? (2017), by Allan Santos da Rosa, a black author from the outskirts of São Paulo. The main objective is to understand how this work revamps rhapsody and fictionally transposes the barrier of invisibility of black bodies, problematizing the historical and social representations of Zumbi. The specific objectives are: to highlight Allan da Rosa's personal and professional trajectories; to outline and analyze the discursive voices present in Zumbi haunts who?, focusing on the central polyphonic subjects, the characters Candê and Tio Prabin; to understand the correspondence between the fictional and the real, at the crossroads of the black bodies portrayed in the literary text; to think about the process of the subject becoming black. The work is created in the articulation of a multiplicity of textual genres that dialogue with each other, and from the collage and remodeling of many stories that intertwine and make the reader get lost in a fabric made up of various spatialities and different historical temporalities. In order to build the theoretical framework and analysis, we drew on authors such as: Chamie (1970) and Sarrazac (2012, 2013), who point out possibilities for reflection on rhapsodic writing; Bâ (2010), to expand our understanding of oral traditions, ancestry and orality; Bakhtin (2010), Canevacci (2004) and Süssekind (2022), to discuss polyphony and chorality; Nascimento (1985), Souza (1983), Munanga (1996, 2013) and Moore (2007), who enable us to think about racism, black movements, quilombo, culture and black identity; Chauí (2008), Candido (2006, 2011) and Cuti (2010), to reflect on ideology, the ways in which reality is represented and how reality crosses literary writings. Through the research, we have come to understand that rhapsodic writing is capable of subverting patterns created by Eurocentric writing and of giving a voice for the subaltern writer to speak and be heard, while appropriating the literary space with a work that represents black-Brazilian literature.